2019
DOI: 10.1159/000489670
|View full text |Cite
|
Sign up to set email alerts
|

Entwicklung einer ressourcenorientierten kognitiv-verhaltenstherapeutischen Gruppenbehandlung für chronisch depressive Patienten: Eine Pilotstudie

Abstract: Hintergrund: Chronisch depressive Patienten profitieren im Durchschnitt weniger von psychotherapeutischen Verfahren als Patienten mit einer akuten oder rezidivierenden depressiven Störung. Eine Augmentierung der Einzeltherapie durch eine ressourcenorientierte Gruppentherapie könnte zu einer Verbesserung der Wirksamkeit führen. Stichprobe: 16 chronisch depressive Patienten nahmen zusätzlich zu einer Einzeltherapie an einer Gruppentherapie mit 12 Sitzungen teil. Methode: Die Schwere der depressiven Symptomatik (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 43 publications
(26 reference statements)
0
2
0
Order By: Relevance
“…This corresponds to the results of previous studies, which also reported no direct benefit of resource-oriented interventions on depression (Bolier et al, 2013; Teismann et al, 2011). Nevertheless, other studies have demonstrated an antidepressant effect of group therapies with and without a resource-activating focus (Dinger et al, 2020; Feng et al, 2012; Guhn et al, 2021; Huntley et al, 2012; Liwowsky et al, 2014; Okumura & Ichikura, 2014; Steinert et al, 2017; Troesken & Renneberg, 2019; Victor et al, 2016; Weiner et al, 2018). However, these studies did not always examine samples consisting exclusively of patients with affective disorders or did not include control groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This corresponds to the results of previous studies, which also reported no direct benefit of resource-oriented interventions on depression (Bolier et al, 2013; Teismann et al, 2011). Nevertheless, other studies have demonstrated an antidepressant effect of group therapies with and without a resource-activating focus (Dinger et al, 2020; Feng et al, 2012; Guhn et al, 2021; Huntley et al, 2012; Liwowsky et al, 2014; Okumura & Ichikura, 2014; Steinert et al, 2017; Troesken & Renneberg, 2019; Victor et al, 2016; Weiner et al, 2018). However, these studies did not always examine samples consisting exclusively of patients with affective disorders or did not include control groups.…”
Section: Discussionmentioning
confidence: 99%
“…Many previous resource-oriented intervention studies used a naturalistic study design and dealt with outpatient and individual settings, whereas randomized, controlled trials including inpatient and group settings are lacking (Bolier et al, 2013; Groß et al, 2012; Troesken & Renneberg, 2019; Victor et al, 2016). Therefore, the aim of the present study was to conduct a randomized, controlled investigation of a newly developed group therapy for resource activation (GTRA) for patients with affective disorders.…”
mentioning
confidence: 99%